The Utilization of Digitalization in Mental Health Screening: Literature Review - Farida, Noor; Adisasmito, Wiku (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2025)
Background: Mental health disorders are one of the contributors to public health problems. Delays in providing mental health services are a major problem in treatment, which is caused by negative stigma from society if someone seeks mental health services. Digitalization in mental health screening is one way that makes early detection of mental health easier. Objective: This paper reviews scientific evidence regarding the use of digitalization in mental health screening. Method: This article was written based on a search for scientific journals carried out through online databases, namely Scopus, Proquest, PubMed, and Scholar, which were published in 2019-2025. Results: Utilization of mental health digitalization can help in early detection and prevent delays in providing mental health services. However, in its use, there are obstacles so that the application is less popular with the public, namely related to lack of trust in the security of personal data in the application, complexity in access, and content that users do not understand. Conclusion: The use of digitalization in mental health screening is an innovation that can improve mental health services, but collaboration from various scientific fields is needed to pay attention to the needs and abilities of users from various aspects.Keywords: Mental Health; Screening; Digitalization.